HRM practices and coorperative behaviors among line managers in quality control circle activities / Johanim Johari - Johari, Johanim (University Publication Centre (UPENA), 2007)
This study examines the relationship between HRM practices and line managers' cooperative behaviors in the QCC activities. The former comprises of training and development, performance appraisal, achievement, career development, and compensation and benefits. This study also analyzes the relationship between demographic factors and respondents' cooperative behaviors. Self-administered questionnaires were distributed to line managers in the manufacturing companies located in the Northern Region of Peninsular Malaysia. Findings indicated that most of the line managers are cooperative with their subordinates. Findings also showed that achievement, training and development, performance appraisal, and compensation and benefit are positively correlated with cooperative behaviors (p<0.05). Career development is not related to cooperative behaviors. The linear regression analysis indicated that achievement has the strongest influence on line managers' cooperative behaviors (p<0.05). Discussions and conclusion emphasized the importance of HRM practices in promoting cooperative behaviors among line managers in QCC activities.